2008
DOI: 10.1007/s00383-008-2197-6
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammatory changes seen in gallbladders of patients with pancreatico-biliary malunion years after transduodenal sphincterotomy: is it a precursor for gallbladder carcinoma?

Abstract: Common pancreaticobiliary channel malunion (PBM) is known to be associated with increased frequency of gallbladder (GB) cancer in adults. Few studies have reported the presence of histological changes in the GB following transduodenal drainage procedures in children with PBM. The aim of this study was to document the histological changes in the GB in children who underwent interval prophylactic cholecystectomy up to 18 years following PBM drainage procedure. All children who underwent open transduodenal sphinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…This bypass should not be performed in benign disease. Similarly, in a small study of children followed after correction of an APBDJ, all patients were found to have chronic inflammatory changes in the gallbladder, which may underlie a predisposition to subsequent GBC in such patients . In addition, in a Japanese study, seven of 26 patients with an APBDJ developed GBC, and seven of 48 patients with GBC were found to demonstrate this anatomical variant …”
Section: Resultsmentioning
confidence: 89%
“…This bypass should not be performed in benign disease. Similarly, in a small study of children followed after correction of an APBDJ, all patients were found to have chronic inflammatory changes in the gallbladder, which may underlie a predisposition to subsequent GBC in such patients . In addition, in a Japanese study, seven of 26 patients with an APBDJ developed GBC, and seven of 48 patients with GBC were found to demonstrate this anatomical variant …”
Section: Resultsmentioning
confidence: 89%
“…The hyperplasia–dysplasia–carcinoma progression is one of the possible mechanisms involved in biliary carcinogenesis. [2526]…”
Section: Introductionmentioning
confidence: 99%